Zebrafish Embryo Toxicity of a Binary Mixture of Pyrethroid Insecticides: d-Tetramethrin and Cyphenothrin - Janthri C. Mendis; Thejani K. Tennakoon; Chanika D. Jayasinghe (Journal of Toxicology)
Pesguard FG161™, a mixture of d-tetramethrin and cyphenothrin (1:3 ratio), is extensively used to achieve rapid control of adult dengue vector, Aedes aegypti, during the disease outbreaks. Both d-tetramethrin and cyphenothrin are synthetic pyrethroids that are known to have adverse effects on non-mammalian organisms such as fish. The present study intended to use zebrafish embryo toxicity model to investigate the toxic effect of the above binary mixture on fish. Particularly, zebrafish embryo toxicity model provides an alternative to acute fish toxicity tests in terms of animal welfare perspective as the embryos are not considered live until 5 days after fertilization. The zebrafish embryos (2 hrs after fertilization) were exposed to a binary mixture of pyrethroids at different concentrations (d-tetramethrin: 0.01 – 1.20 μmolL-1 and cyphenothrin: 0.03 – 3.20 μmolL-1) for 24, 48, and 72 hrs at room temperature (26°C) according to the OECD guideline no. 236. Percentage mortality of embryos were calculated by observing the lethal endpoints and LC50 values were calculated for each time interval employing the probit analysis. This binary mixture was highly toxic to zebrafish embryos and was found to be concentration and time dependent. LC50 values at 24 hrs (d-tet: 0.58 μmolL-1, cyp: 1.74 μmolL-1) were significantly reduced in 48 hrs (d-tet: 0.11 μmolL-1, cyp: 0.33 μmolL-1) and 72 hrs (d-tet: 0.03 μmolL-1, cyp: 0.09 μmolL-1). Coagulation of embryos was the most common lethal effect observed and lack of somite formation and lack of heartbeat were also observed. The present study revealed that the binary mixture is highly toxic to zebrafish embryos even when based on nominal concentrations. Hence, extensive use of these pesticides could be detrimental to fish population and integrated vector control methods which involve the minimum use of insecticides are recommended. Further, this study highlights the applicability of zebrafish embryo toxicity model as an alternative method to investigate the toxicity of pyrethroids to fish.